2017
DOI: 10.1103/physreva.96.062315
|View full text |Cite
|
Sign up to set email alerts
|

Dissipative preparation of steady Greenberger-Horne-Zeilinger states for Rydberg atoms with quantum Zeno dynamics

Abstract: Inspired by a recent work [Reiter, Reeb, and Sørensen, Phys. Rev. Lett. 117, 040501 (2016)], we present a simplified proposal for dissipatively preparing a Greenberger-Horne-Zeilinger (GHZ) state of three Rydberg atoms in a cavity. The Z pumping is implemented under the action of the spontaneous emission of Λ-type atoms and the quantum Zeno dynamics induced by strong continuous coupling. In the meantime, a dissipative Rydberg pumping breaks up the stability of the state |GHZ+ in the process of Z pumping, makin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 48 publications
(58 reference statements)
0
32
0
Order By: Relevance
“…The generation and analysis of n-photon GHZ entanglement are highly demanding. To date, various efficient methods to generate the GHZ entanglement have been developed for different physical systems [45][46][47][48][49][50][51][52][53]. In photonic systems, an eight-photon GHZ state and a three-photon high-dimensional GHZ state have been experimentally demonstrated [54][55][56][57] by performing quantum fusion combined with post-selection operations and quantum interference [28,58,59].…”
Section: Introductionmentioning
confidence: 99%
“…The generation and analysis of n-photon GHZ entanglement are highly demanding. To date, various efficient methods to generate the GHZ entanglement have been developed for different physical systems [45][46][47][48][49][50][51][52][53]. In photonic systems, an eight-photon GHZ state and a three-photon high-dimensional GHZ state have been experimentally demonstrated [54][55][56][57] by performing quantum fusion combined with post-selection operations and quantum interference [28,58,59].…”
Section: Introductionmentioning
confidence: 99%
“…|5p 1/2 . The effective twophoton Rabi frequency is achieved to be a reasonable value Ω 0 = 2π × 2.5MHz [27], with which the ground state |1 is coupled to the |r by a big detuning ∆ = 2π × 36MHz, giving rise to the characteristic frequency of system ω 0 = Ω 2 0 /4∆ = 0.273MHz. In the real implementation two atoms can be trapped separately with an interatomic distance R c = 9.5µm for realizing a considerable vdWs interaction U rr = 2π × 72MHz, driven by a periodically time-dependent laser beam Ω(t) with amplitude Ω 0 and modulation frequency ω = ω 0 = 0.273MHz.…”
Section: Feasibility and Ways For Further Facilitationmentioning
confidence: 98%
“…Nevertheless this approach simultaneously suffering from the complexity of energy levels and laser fields combining with Rydberg interactions [20][21][22], still has not been realized in experiment. * jqian1982@gmail.com Other alternative approaches are proposed by combining an optical cavity to trigger the entanglement formation, because the cavity decay treating as an auxiliary loss channel towards the target state, can permit a reduced stabilization time that is smaller than tens of microseconds depending on the absolute value of cavity mode coupling [23][24][25][26][27]. More recently an intriguing improvement for a ten-times faster generation of steady entanglement in a cavity is suggested by using pulse modulation, achieving an exponentially enhancement for the atom-cavity coupling [22].…”
Section: Introductionmentioning
confidence: 99%
“…It enables tunable, anisotropic interactions and provides the possibility to study the novel exotic many-body physics [19][20][21][22][23] In addition, the combination of interatomic Rydberg interactions and two-photon detuning leads to an opposite effect, the Rydberg antiblockade, which theoretically predicted by Ates et al [24] and was experimentally observed by Amthor et al [25]. The Rydberg antiblockade can achieve the multiple Rydberg excitations while restrain the Rydberg blockade, and its exploration is of particular interest not only for multiqubit logic gates [26], but also for preparations of quantum entanglement [27][28][29][30][31], e.g. Carr et al analyzed an approach to obtain high fidelity entanglement and antiferromagnetic states by Rydberg antiblockade [27].…”
Section: Introductionmentioning
confidence: 99%
“…Carr et al analyzed an approach to obtain high fidelity entanglement and antiferromagnetic states by Rydberg antiblockade [27]. Quite recently, our group made use of the cooperation between Rydberg antiblockade, quantum Zeno dynamics, and atomic spontaneous emission to prepare the tripartite GHZ state and W state, respectively * Corresponding author: shaoxq644@nenu.edu.cn [30,31]. Moreover, by virtue of the Rydberg-antiblockade effect and the Raman transition, we have devised a mechanism of ground-state blockade to generate the high-fidelity entanglement [32].…”
Section: Introductionmentioning
confidence: 99%